USING THINK PAIR SHARE TEACHING STRATEGY TO STUDENTS IN TEACHING SPEAKING - Melikhah Nur Maulani; H. Khalimi Romansyah; M. Ita Atiyawati (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2019)
Many people may find some difficulties to share their ideas or opinion through oral language. Even though they have something to speak, they do not know how to express it. They also have problems related to lack of participation and low motivation in speaking. Therefore, a teacher should select the best technique that can encourage students and increase their motivation to speak. The teacher can use “Pair Work” to teach English speaking. This technique demands students to be active to speak based on the material has been given. Through this technique, students should practice to speak in order to give agreeing and disagreeing opinion. By apliying this technique in speaking class, it will make the class fun and interesting. The objective of this paper is to explain how to use pair work technique in teaching speaking to junior high school students in Smpn 1 Plumbon.